Identification of Active Chemical Compounds of Honey from Some Regions in Indonesia - La Ode Sumarlin; Nur Enita; Farhan Riza Afandi; Ahmad Fathoni (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
Bees produce honey from plant nectar, plant secretions, and excretions of plant-sucking insects. Indonesian local honey contains active compounds that have the potential effect as antioxidant and anticancer. The composition and biological effects of honey vary depending on the flower sources; seasonal and environmental factors can also influence the composition and the physical products. This research was conducted to identify the chemical compounds found in several honey samples produced by beekeepers in Indonesia with LCMS/MS method and to determine the profiles of the honey from Indonesia with the Chemspider and MassBank Database. Honey samples were collected from several regions in Indonesia. The results of the analysis showed that the honey’s diastase number vary from region to region and showed that the HMF contents are relatively low. The compounds that were allegedly found through LCMS/MS analysis include and have been traced based on literature studies had bioactive activity and beneficial to health, include: millefin (potential for treating heart disease and cancer), mangiferin (anti-inflammatory, anti-diabetes, immunomodulators, anti-tumor, antioxidants), rhamnetin (anti-inflammatory), tricin (antioxidant-like), acacetin (inhibit tumor angiogenesis agents), aurantiamide acetate (antiviral or anti-inflammatory, therapeutic agent for the treatment of influenza), salvigenin (controlling inflammation, acute and chronic pain), brucine (modulates anti-inflammatory and analgesic properties), dehydrocostus lactone (anti-inflammatory), santonin (anthelmintic activity), dimethylesculetin (bilirubin clearance), imidazole 4- acetic acid (neuropharmacological properties), propafenone (antiarrhythmic), yohimbine (affected sexual performance), Velutin (anti-inflammatory), narigenin (linked to cardiovascular disease protection). Eventually, honey is is such a natural product with a number of salient therapeutic properties. However, there are still components that were found but their roles cannot be described in detail. Therefore, it is recommended that further meticulous studies should bring to light the other hidden properties of the honey compounds.